contestada

Simplify this equation: −3(−5 + x) ≥ 3 Show all steps
I'll give brainliest to the first correct answer with an explanation and showed steps!

Respuesta :

Answer:

Step-by-step explanation:

The safest way to begin is to remove the brackets.

-3 * - 5  -3x  ≥  3            Combine the left.

15 - 3x ≥  3                     Subtract 15 from both sides

-3x ≥ -12                         Divide by -3

x ≤ -12/-3

x ≤ 4

Notice when the ≥ turned around to ≤. It can only do this when you divide or multiply to get rid of a coefficient in front of number followed by a variable.

I've made you a graph of -3(-5 + x) ≥ 3. Notice the graph shows that the largest value can be 4 just as the solution suggests.  

     

Ver imagen jcherry99